Is it possible to have scientific knowledge of Being? - Polikarpov, Vladimir A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Being was always the subject of metaphysics. At the end of the XX century, it entered the orbit of the interests of the natural sciences. For example, the causal interpretation of quantum mechanics, David Bohm, which opens the possibility of assuming the existence of more subtle levels of reality, presupposes a phyton vacuum as the basis of the visible world. A similar scheme is suggested by the concept of the Higgs field, or the theory of substantial flows of A. P. Levich. The theory of temporal feedback works with a similar model. The article shows how, using the program of comprehension of Being proposed by M. Heidegger, one can approach the experimental study of Being within the framework of the theory of temporal feedback. The author starts from the idea of M. Heidegger that Being is of a purely human dimension. Only the elucidation of the essence of human existence reveals the essence of Being itself. The reflection of the essence of Being in human existence presupposes the use of psychological methods. The author substantiates the application of the psychosemantic experiment.